El juego combinativo ofensivo en el balonmano de élite: diferencias por género mediante análisis de coordenadas polares - Quiñones Rodriguez, Y.; Morillo-Baro, J. P.; Reigal, R. E.; Morales-Sánchez, V.; Vázquez-Diz, J. A.; Hernández-Mendo, A. (Cuadernos de Psicología del Deporte, 2020)
The aim of this study was to analyse by means of polar coordinate analysis the effectiveness of the behaviours shown during offensive combinative play in elite male and female handball in Spain. Ten teams belonging to the ASOBAL League were observed in the male category and the Copa La Reina in the female category. An observational tool designed ad hoc by means of a mixed system of field formats and a system of exhaustive and mutually exclusive categories (E/ME) was used, formed by 12 criteria and 62 categories with a Nomothetic/Punctual/Multidimensional observational design. The unit of analysis was the positional attack. Four focal behaviours were selected: simple collective tactical means, combination of tactical means, transformations and advantageous launch. An analysis of polar coordinates was carried out with the HOISAN software, considering the modules =1.96 to be significant. The results showed differences in the flow of behaviors between the feminine and masculine game. The feminine category with accentuated actions in the right zone of the field. The most consistent results coincide with the first forty minutes of play and with the use of simple collective tactical means and combinations. In the men's category, good tactical performance was evident throughout the game. The combination of the collective tactical means showed a direct relation with the victory. In both categories the transformation of the systems induces the endings in forced throws. The differences suggest to intervene in the preparation of both categories with a specific orientation towards the improvements in the performance of the combined positional game.